1997
DOI: 10.1111/j.1399-6576.1997.tb04668.x
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion of pethidine in lidocaine for infiltration improves analgesia following tonsillectomy in children

Abstract: Inclusion of a low dose of pethidine in lidocaine for tonsillar infiltration improves pain relief after tonsillectomy in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 16 publications
0
12
0
1
Order By: Relevance
“…A previous study by Elhakim et al [7] demonstrated that administration of lidocaine combined with pethidine to the peritonsillar fossa pre-operatively could provide considerable postoperative pain relief in infants and children. We hypothesised that the inclusion of pethidine and bupivacaine would offer more reliable pain relief, at least in the early postoperative period, because of the more prolonged local anaesthetic effect of bupivacaine.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A previous study by Elhakim et al [7] demonstrated that administration of lidocaine combined with pethidine to the peritonsillar fossa pre-operatively could provide considerable postoperative pain relief in infants and children. We hypothesised that the inclusion of pethidine and bupivacaine would offer more reliable pain relief, at least in the early postoperative period, because of the more prolonged local anaesthetic effect of bupivacaine.…”
Section: Discussionmentioning
confidence: 99%
“…In the study of Elhakim et al [7] electrodissection rather than snare dissection was used for tonsillectomy. The introduction of an electrodissection surgical technique has virtually eliminated immediate postoperative haemorrhage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Combined assessment by child, nurse, and parents as applied in our study may be a valid means of improving the validity of pain scoring in children. 22 The long-term administration of corticosteroids is associated with adverse events, such as increased risk of infection, delayed wound healing, glucose intolerance, adrenal suppression, and a vascular necrosis of the hip or other joints. Although a single dose of dexamethasone is considered safe, further studies with longer follow-ups are indicated.…”
Section: Figure 1 Median Children's Hospital Eastern Ontario Painmentioning
confidence: 99%
“…In our study we used 4 mg/kg dose of 10% lignocaine aerosol in tonsillar fossa in both study group B and C and no lignocaine toxicity noted in any patient. In their study, 19,20 they successfully used 10% lignocaine spray which administered topically in tonsillar bed to alleviate immediate post-operative pain and discomfort in tonsillectomy patients.…”
Section: Discussionmentioning
confidence: 99%